The Miraculous Untranslatable Qur’an - CHAGOUR, Amal (Journal of Human Sciences, 2018)
This paper attempts to highlight the fact that much is lost when the Qur’an is encountered in translation and that it is out of the question for a perfect accurate translation of the most eloquent of all speeches to be attained. This research measures faithfulness and explores the possibility of preserving the meanings, including possible scientific implications, if literal translation were adopted. This was done through the analysis of some selected words in five widespread translations. Results show non-equivalence and unsuccessfulness in transferring accurately some features of the Qur’an’s inimitability or ‘I’jaz’. Thereafter, the study draws the conclusion that the Qur’an could be considered untranslatable and literal translation is key to approximating the unmatchable divine words.